2022
DOI: 10.3389/fevo.2022.765388
|View full text |Cite
|
Sign up to set email alerts
|

Odor-Pollution From Fungicides Disrupts Learning and Recognition of a Common Floral Scent in Bumblebees (Bombus impatiens)

Abstract: Background and AimsBumblebees provide vital pollination services to both natural and agricultural ecosystems. Consequently their declines in species-diversity and population size over the last five decades is alarming. Direct contributors to these declines include pesticides, habitat loss, and disease. However, given that colony fitness is linked to foraging success, successful conservation requires mitigation of any anthropogenic practices that negatively impact foraging. Previous work has shown that agrochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…A subsequent study found variable effects of diesel-driven odor pollution dependent on floral color [14]. Interestingly diesel exhaust contains sulfurous components - an attribute shared by several fungicides that have also been shown to disrupt bumblebee behavior on a local scale [11,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A subsequent study found variable effects of diesel-driven odor pollution dependent on floral color [14]. Interestingly diesel exhaust contains sulfurous components - an attribute shared by several fungicides that have also been shown to disrupt bumblebee behavior on a local scale [11,12].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, anthropogenic activity can indirectly impact sensory signals that are utilized by bumblebees while foraging for floral resources. For example, negative effects of human activity on floral-scent signaling and reception include a reduction of distance traveled by floral scent [6,7], increased foraging times [8], decreases in floral scent recognition [9][10][11][12], and alterations of flower visitation rates [13,14]. These negative effects are potentially exacerbated by asymmetric impacts of sublethal pesticide exposure with odor-learning,but not color-learning, being impaired [15].…”
Section: Introductionmentioning
confidence: 99%
“…Another potential explanation for the lower visit frequency could be the direct effect of fungicides on altering the taste, as shown with sugar water [ 70 ], which in turn can influence the foraging behaviour of bees. Furthermore, the scent of the used fungicides could have interfered with the recognition of common floral scent [ 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, actual strawberry plants were used and last sprayed a few days before the trials leading to more random, but also natural variation in terms of olfactory and visual traits, compared to artificial flowers or scent feeders, as used in several other studies on strawberry pollination (e.g., [ 15 , 71 ]. Another critical aspect of fungicide use in crop cultivation that needs to be considered is that the fungicide treatment of the plants may affect not only the foraging behaviour of bumblebees but also the physiology of the insects.…”
Section: Discussionmentioning
confidence: 99%
“…Although these chemicals control pests and plant pathogens, non-target insects such as bees and butterflies encounter them while foraging from chemical-laden plants. These chemicals can also have non-consumptive effects, such as creating odor pollution, which makes olfactory-based tasks such as foraging and navigation challenging for insects 8 , 9 . However, once consumed, they have detrimental impacts on non-target insect health, which can persist for generations after exposure 10 14 .…”
Section: Introductionmentioning
confidence: 99%